2013
DOI: 10.1016/j.jep.2012.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Antiophidic activity of the extract of the Amazon plant Humirianthera ampla and constituents

Abstract: Altogether, our results give support for the popular use of HA extracts in cases of accidents with snakes, suggesting that it can be used as an adjunct in the management of venomous snakebites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
3
27
0
4
Order By: Relevance
“…Among these hyaluronidase is responsible for the spreading of poison (da Silveira et al, 2007a) and phospholipase D, referred to in the literature as sphingomyelinase D or phosphodiesterase D due to its ability to hydrolyze sphingomyelin (da Silva et al, 2004) are the main enzymes described. In this work it was shown that the venom of L. intermedia presents sphingomyelinase activity in high concentrations, but does not show phospholipase A 2 activity, as demonstrated for venoms of different species of snakes (Fuly et al, 2007;Strauch et al, 2013). We would have expected a more linear response, but the sphingomyelinase D activity observed only in the highest concentration (100ug/mL) can be explained by the use of venom pool of different spiders Loxosceles intermedia diluted in physiological saline, being this concentration related to the total protein, it is not possible to affirm the exact concentration of the enzyme sphingomyelinase in relation to protein concentration tested.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Among these hyaluronidase is responsible for the spreading of poison (da Silveira et al, 2007a) and phospholipase D, referred to in the literature as sphingomyelinase D or phosphodiesterase D due to its ability to hydrolyze sphingomyelin (da Silva et al, 2004) are the main enzymes described. In this work it was shown that the venom of L. intermedia presents sphingomyelinase activity in high concentrations, but does not show phospholipase A 2 activity, as demonstrated for venoms of different species of snakes (Fuly et al, 2007;Strauch et al, 2013). We would have expected a more linear response, but the sphingomyelinase D activity observed only in the highest concentration (100ug/mL) can be explained by the use of venom pool of different spiders Loxosceles intermedia diluted in physiological saline, being this concentration related to the total protein, it is not possible to affirm the exact concentration of the enzyme sphingomyelinase in relation to protein concentration tested.…”
Section: Discussionmentioning
confidence: 75%
“…The evaluation of these activities had not been described in the literature using similar methodologies to the venom of L. intermedia. Thus, our work can represent an important contribution to characterization and screening for the study of antagonists of the actions of this venom (De Oliveira et al, 2014;Strauch et al, 2013). C57BL/6, BALB/c and Swiss mice represent different mouse strains with similar genetic characteristics, phenotypes completely different and distinct potential to respond the same stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the direct polyanion's ability to neutralize the venom toxins with positive charges, and the second effect is the inhibition of the inflammatory response evaluated by the antagonism of phospholipase activity and the decreased local muscle leukocyte MPO induced by the venom components. Previous observations demonstrated that the presence of inflammatory cells is related with myonecrosis induced by snake venoms, and the treatment with dexamethasone or plant extract decreases the MPO and inflammation, as well as the muscle damage (Patrão-Neto et al, 2013;Strauch et al, 2013). The increase of leukocytes observed in groups treated with fucCS may be explained by a possible increase in leukocyte mobilization from bone marrow, induced by inflammatory response after venom injection, a process in which glycosaminoglycans can be important (Gordon et al, 1987;Patrão-Neto et al, 2013;Strauch et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…In the Amazon region, for example, indigenous peoples use macerated leaves of Pentaclethra macroloba as an ointment for topical application on the site of bite (Da Silva et al, 2005). Concerning B. atrox, it has been reported that extracts from Marsypianthes chamaedrys reduced venom induced leukocyte migration (Magalhães et al, 2011), flowers extracts of Peltodon radicans inhibited the venom induced edema (Da Costa et al, 2008) and Humirianthera ampla extracts reduced 75% of the myotoxic effect of the venom (Strauch et al, 2013). However, the majority of plant species used in Amazonian folk medicine remains without scientific validation.…”
Section: Introductionmentioning
confidence: 99%